2021
DOI: 10.17660/ejhs.2021/86.3.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maturation on chemical composition and harvest of fruits of diverse elderberry interspecific hybrids

Abstract: What is the expected impact on horticulture? • the most appropriate harvest time in order to assure the best fruit quality. • The breeders will be able to select the best genotypes for propagation or hybridisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Although the phytochemicals in elder products have complex polypharmacological actions, the most popular of these is their antioxidant effect. A recent study showed that the antioxidant activity of elderflower and elderberry extracts resulted from the presence of phenolic compounds, mainly flavonols, phenolic acids, and anthocyanins [ 29 , 30 , 31 ]. Furthermore, more and more researchers highlight the potential anti-aging mechanisms of polyphenols, including antioxidant signaling, preventing cellular senescence, targeting microRNA, influencing NO bioavailability, and promoting mitochondrial function [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the phytochemicals in elder products have complex polypharmacological actions, the most popular of these is their antioxidant effect. A recent study showed that the antioxidant activity of elderflower and elderberry extracts resulted from the presence of phenolic compounds, mainly flavonols, phenolic acids, and anthocyanins [ 29 , 30 , 31 ]. Furthermore, more and more researchers highlight the potential anti-aging mechanisms of polyphenols, including antioxidant signaling, preventing cellular senescence, targeting microRNA, influencing NO bioavailability, and promoting mitochondrial function [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In its report EMA/HMPC/44208/2012, the European Medicines Agency [7] notes that the fruit of S. nigra contains several components that may contribute to pharmacological activity, with various phenolic compounds among them, such as anthocyanins and flavonols, possessing notable antioxidant activity. However, the concentration of polyphenols varies depending on several factors such as the genotype, the environmental conditions or the degree of ripening of the fruit [3,[10][11][12][13][14][15], so the content of this group of nutraceuticals shows wide variability. Thus, differences of more than 100% have been reported in the content of the different phenolic compounds for varieties in the same location [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, differences of more than 100% have been reported in the content of the different phenolic compounds for varieties in the same location [3,5]. It has also been proven that, in the ripe fruit, anthocyanins are the main extractable phenolic compounds, Antioxidants 2023, 12,1986 2 of 16 while in the green fruit, this family of flavonoids is not present, and flavonols and phenolic acids predominate [13,16,17]. Imenšek et al [13] have shown that when the fruits are overripe (more than 90% of the fruits are shrivelled due to moisture loss) the nutritional quality (sugars and organic acids) of elderberries decreases, which is why the authors proposed harvesting the fruit when it is completely ripe or even before the complete maturation of all the berries in the bunch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations